Cyclophilin J PPIase Inhibitors Derived from 2,3-Quinoxaline-6 Amine Exhibit Antitumor Activity - Zhao, Xuemei; Xia, Chengcai; Wang, Xiaodan; Wang, Hao; Xin, Ming; Yu, Long; Liang, Yulong (Frontiers in Pharmacology, 2018)
Cyclophilin J (CyPJ), also called peptidylprolyl isomerase like 3 (PPIL3), has been identified as a novel member of the cyclophilin family. Our previous research has resolved the three-dimensional structure of CyPJ, and demonstrated the peptidylprolyl cis-trans isomerase (PPIase) activity of CyPJ, which can be inhibited by the common immunosuppressive drug cyclosporine A (CsA). Importantly, CyPJ is upregulated in hepatocellular carcinoma (HCC) and promotes tumor growth; CyPJ inhibition by CsA or siRNA-based knockdown results in a remarkable suppression of HCC. These findings suggest CyPJ may be a potential therapeutic target for HCC, and discovery of relevant inhibitors may facilitate development of a novel CyPJ-based targeting therapy. However, apart from the common inhibitor CsA, CyPJ has yet to be investigated as a target for cancer therapy. Here, we report structure-based identification of novel small molecule non-peptidic CyPJ inhibitors and their potential as antitumor lead compounds. Based on computer-aided virtual screening (VS), in silico, and subsequently surface plasmon resonance analysis, 19 potential inhibitors of CyPJ were identified and selected for further evaluation of PPIase CyPJ inhibition in vitro. Thirteen out of 19 compounds exhibited notable inhibition against PPIase activity. Among them, the compound ZX-J-19, with a quinoxaline nucleus, showed potential for tumor inhibition; thus, we selected it for further structure-activity optimization. A total of 22 chemical derivatives with 2,3-substituted quinoxaline-6-amine modifications were designed and successfully synthesized. At least two out of the 22 derivatives, such as ZX-J-19j and ZX-J-19l, demonstrated remarkable inhibition of tumor cell growth, comparable to CsA but much stronger than 5-fluorouracil (5-FU). These results indicate that these two small molecules represent novel potential lead compounds for CyPJ-based antitumor drug development.